Evaluating the quality improvement impact of the Global Tracheostomy Collaborative in four diverse NHS hospitals - McGrath, Brendan A (BMJ Qual Improv Rep, 2017)
Tracheostomies are predominantly used in Head & Neck Surgery and the critically ill. The needs of these complex patients frequently cross traditional speciality working boundaries and locations and any resulting airway problems can rapidly lead to significant harm. The Global Tracheostomy Collaborative (GTC) was formed in 2012 with the aim of bringing together international expertise in tracheostomy care in order to bring about rapid adoption of best practices and to improve the quality and safety of care to this vulnerable group. The primary aim of this project was to improve the safety and quality of care delivered to adult patients with new or existing tracheostomies. We implemented changes guided by the GTC using multiple PDSA cycles over a 12-month period. Interventions were across three themes: educational, patient-centred (earlier vocalisation and enteral intake) and organisational. We hypothesised that systematic healthcare improvements would reduce the severity of harm resulting from tracheostomy-related safety incidents and improve surrogate markers of the quality of patient-centred care. Furthermore, we hypothesised that raising the quality and safety of healthcare services would lead to more efficient care, measured by earlier tracheostomy decannulation times and reduced hospital lengths of stay. This Quality Improvement project implemented the GTC into four diverse NHS Trusts in Greater Manchester. Key drivers implemented included multidisciplinary tracheostomy steering groups, ward rounds and bedside teams, standardisation of tracheostomy protocols, staff education and meaningful involvement of patient and family. Surrogates for the quality and safety of care were captured for all patients using a bespoke database. Implementing the GTC into four NHS Trusts rapidly and positively impacted on patient safety metrics and surrogates for the quality of care delivered. It is likely that the comprehensive resources of the GTC will be of benefit to other NHS hospitals and indeed other healthcare systems around the world.